Foliar Silicon Spray to Strawberry Plants During Summer Cutting Propagation Enhances Resistance of Transplants to High Temperature Stresses - Xiao, Jie; Li, Yali; Jeong, Byoung Ryong (Frontiers in Sustainable Food Systems, 2022)
Silicon (Si) has been reported to benefit plant growth and stress resistance. This work aimed to find out an optimal method of Si application to enhance the resistance of strawberry (Fragaria × ananassa Duch.) transplants to high temperatures, commonly experienced in the summer when strawberries are propagated for greenhouse production in Korea. Plants of strawberry ‘Sulhyang’, ‘Maehyang’, and ‘Kuemsil’ were subjected to one of five treatments before the cutting propagation: no treatment (control), substrate dressing of a water-soluble silicate fertilizer, substrate drench of 75 mg·L−1 Si (from potassium silicate) to the mother plants, or foliar spray of 75 mg·L−1 Si to either the mother plants or daughter plants. Half of the daughter plants in each treatment received continued Si supply through either substrate dressing of a water-soluble silicate fertilizer, substrate drench, or foliar spray after the cutting propagation. A high temperature (43°C) resistance test was conducted in plant growth chambers for 7 days with a 16-hour photoperiod with a light intensity of 300 mmol∙m-2∙s-1 PPFD. During the high temperature test, the rate of decline in the photosynthesis was lower in plants treated with Si than in the control. After the high temperature test, it was observed that Si application significantly increased the shoot fresh weight of transplants. Moreover, the contents of sugars, proteins, and enzymatic (CAT, SOD, POD, and APX) and non-enzymatic (anthocyanin and proline) antioxidants were higher in plants treated with Si throughout the entire propagation period, compared to the control and plants only treated with Si before or after the cutting propagation. Overall, Si application promoted the growth of the transplants regardless of the application method used. Moreover, spraying the daughter plants with Si, and continually spraying the transplants were found to be the best and is recommended to increase the resistance of strawberry to high temperatures during propagation.